Global strategic developments a futuristic vision (Emirates Center for Strategic Studies and Research, 2012)
The world today faces numerous challenges, including the fallout from the financial crisis and varied and diverse examples of violence and conflict across the globe. This book offers an examination of these developments, providing an exploration of the future of the global system and its international powers and organizations.